IoT -development of a home automation system - Lim, Ming Wei (Nanyang Technological University, 2022)
Home Automation provides comfort and quality of life. With this system it allows the user to control house appliances via a smartphone. A smartphone application can be used to monitor and control home appliances. In this paper, we embark on a prototype of such implementation of Smart Home Automation using WIFI technology embedded in ESP8266 and ESP32. Both ESP8266 and ESP32 have powerful on-board processing capabilities and has a full TCP/IP stack. It provides the ability for data processing, reading, and controlling of GPIOs